Evaluation of isotope contents of plutonium in reactor emissions by gamma-radiation of ¹⁰⁶Ru, ¹¹¹Ag and ¹²⁵Sb - Bykov, V.T.; Elmansury, A.M.; Olejnik, S.N.; Rudak, E.A.; Tulubtsov, A.Ya.; Vodin, A.N.; Yachnik, O.I. (Вопросы атомной науки и техники, 2005)
It is offered to use nuclides ¹⁰⁶Ru, ¹¹¹Ag and ¹²⁵Sb for evaluation of transuranium elements content in the spent fuel of HPOR-1000 reactor. It is found that ¹²⁵Sb is the most suitable for estimations of emergency reactor emissions. The developed formalism can be applied for reactors such as WWR. Пропонується використовувати нукліди ¹⁰⁶Ru, ¹¹¹Ag і ¹²⁵Sb для визначення змісту трансуранових елементів у відпрацьованому паливі реактора РБМК-1000. Для оцінок аварійних реакторних викидів найбільш підходящим є ¹²⁵Sb. Розроблений формалізм оцінок може бути застосований для реакторів типу ВВЕР. Предлагается использовать нуклиды ¹⁰⁶Ru, ¹¹¹Ag и ¹²⁵Sb для определения содержания трансурановых элементов в отработанном топливе реактора РБМК-1000. Для оценок аварийных реакторных выбросов наиболее подходящим является ¹²⁵Sb. Разработанный формализм оценок может быть применен для реакторов типа ВВЭР.